Myositis-associated antibodies predict the severity of lung involvement in adult patients with inflammatory myositis − a cohort study of 70 adult patients with myositis in a single center - Marklund, Josefin; Hanna, Balsam; Jin, Tao; Pullerits, Rille (Frontiers in Medicine, 2024)
Introduction Idiopathic inflammatory myopathies (IIMs) encompass a diverse group of diseases characterized by considerable variability in clinical manifestations, antibody profiles, and responsiveness to immunosuppressive therapies. This study aimed to investigate the association between organ involvement and distinct myositis autoantibodies in individuals with IIM in a single-center cohort. Methods Patients with ICD diagnoses M33.1, M33.2, M33.9, or M609 who (1) had been tested with Euroline blot assay for myositis autoantibodies and (2) met the classification criteria of definite/probable polymyositis (PM) or dermatomyositis (DM), anti-synthetase syndrome (ASS), or inclusion body myositis (IBM) were included. Medical journals were retrospectively examined with respect to clinical disease features. Results Seventy patients (median age 58 years; 66% females) were included and represented the following diagnosis: PM (n = 23), DM (n = 21), ASS (n = 23), and IBM (n = 3). Most of the patients (87%) presented a muscle biopsy indicative of myositis. The presence of autoantibodies was as follows: myositis-specific antibodies, MSA (n = 53), myositis-associated antibodies, MAA (n = 33), both MSA + MAA (n = 24), MSA only (n = 29), MAA only (n = 9), no MSA, or MAA (n = 8). Anti-Jo-1 was the most common MSA (19%), whereas the most common MAA was anti-Ro/SSA52 (31%). We observed a significant association between antibody patterns and lung disease. In our cohort, 47% of the patients in the whole study group, 86% of patients with anti-SSA52, and 100% with anti-Jo-1 had pulmonary involvement. Patients with both MSA and MAA had a higher incidence of lung disease and decreased CO-diffusion capacity. This was especially prominent in anti-Ro/SSA52-positive patients. Interestingly, none of the patients suffered from lung disease if only antibodies against Mi-2α, Mi-2β, NXP2, HMGCR, and TIF1γ were present or no MSA/MAA were detected. Discussion: The simultaneous presence of both MAA and MSA indicates an increased risk of lung involvement in patients with inflammatory myopathies. The presence of any MAA, and especially anti-Ro/SSA52, is associated with more severe pulmonary disease. Our data suggest that MAA antibodies might be relevant markers for early detection and treatment of lung involvement in IIM.